1995
DOI: 10.1044/1058-0360.0401.25
|View full text |Cite
|
Sign up to set email alerts
|

Normal Speech and Hearing by Age 5 as a Goal for Children With Cleft Palate

Abstract: The authors report the results of a 4-year project to influence speech and hearing outcomes, employing direct program-management strategies with both multidiscipline professionals and family members of children born with oral clefts. Early and continuing speech and hearing diagnosis (12–60 months), parent education as speech aides, timely professional speech habilitation, including use of temporary speech appliances, and early medical care for ears were used in seeking a goal of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The results emphasize the recurrent periods of auditory deprivation the subjects experienced during the critical window of opportunity for early language acquisition. These findings are in agreement with the studies of Blakely and Brockman (1995) and Russell and Grunwell (1993) who also found varying hearing levels associated with recurrent attacks of otitis media with effusion throughout infancy and early childhood as characteristic of their subjects with cleft lip and palate.…”
Section: Hearing Abilitiessupporting
confidence: 92%
“…The results emphasize the recurrent periods of auditory deprivation the subjects experienced during the critical window of opportunity for early language acquisition. These findings are in agreement with the studies of Blakely and Brockman (1995) and Russell and Grunwell (1993) who also found varying hearing levels associated with recurrent attacks of otitis media with effusion throughout infancy and early childhood as characteristic of their subjects with cleft lip and palate.…”
Section: Hearing Abilitiessupporting
confidence: 92%
“…We recognize the heterogeneic reality of children with cleft palate but have not identified all the factors that contribute to it (Riski, 1995). With more attention to the description of emerging phonologic development, the structural capability of each child can perhaps be determined earlier so appropriate and timely intervention can occur and we can increase the numbers of younger persons with cleft palate who develop acceptable articulation and phonologic skills (Blakeley and Brockman, 1995).…”
Section: Articulationmentioning
confidence: 99%